Using Duolingo for Learning Vocabulary: Perspectives of English Education Study Program Students of Sriwijaya University - Nurjanah, Nabilah Faqih; ⁠Fiftinova, ⁠Fiftinova (JELITA, 2026)
This study examines Sriwijaya University students in the English Education Study Program's perspectives on the use of Duolingo for vocabulary learning. Through qualitative research involving interviews and a closed-ended questionnaire, the findings indicate that students hold a positive view of Duolingo, particularly appreciating its gamified approach, which makes vocabulary expansion enjoyable and motivating. Students unanimously agree that the application is accessible and reports benefits such as the ability to practice at any time, improved word retention, and increased confidence. However, some challenges were identified, including unclear word meanings (90.5% agreement), limitations in comprehensive vocabulary learning (95.3% agreement), awkward translations, the restrictive heart system that halts practice after mistakes, and problems with speech recognition. The study concludes that while Duolingo is an effective tool for motivation and vocabulary practice, it should complement traditional teaching methods to enhance grammar and contextual language use. Recommendations include improving contextual learning within the app and modifying the strict "heart system."